Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1038/sj.ijo.0800557
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia in female overweight and obese patients. Relation to anthropometric and endocrine factors

Abstract: OBJECTIVE: To characterize serum lipid abnormalities in overweight and obese female patients and to quantify the relative importance of associated factors. METHODS: Cross sectional study at the ®rst visit to the out-patient department. 237 consecutive overweight and obese female patients (age 31 AE 14 y, body mass index (BMI) 34.2 AE 6.0 kg/m 2 ) were studied. Evaluation included a questionnaire-based assessment of dietary and physical activity habits, determination of anthropometric indexes (BMI, abdominal/th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The association between dyslipidaemia and obesity has long been identified. In 1998, Martins J. et al observed dyslipidaemia being common among mild to moderate obese woman [65]. In a study of 13,770 2-17 year -old-Chinese-children Li Y. et al found that the odds of prevalent dyslipidaemia was 1.76 times higher in overweight than average-weight ones.…”
Section: Accepted Manuscript Dyslipidaemiamentioning
confidence: 99%
“…The association between dyslipidaemia and obesity has long been identified. In 1998, Martins J. et al observed dyslipidaemia being common among mild to moderate obese woman [65]. In a study of 13,770 2-17 year -old-Chinese-children Li Y. et al found that the odds of prevalent dyslipidaemia was 1.76 times higher in overweight than average-weight ones.…”
Section: Accepted Manuscript Dyslipidaemiamentioning
confidence: 99%
“…An involvement of IGF-1 as a mediator in this GH effect on leptin is not supported by the present study as the effects on leptin levels of centrally applied IGF-1 are not very impressive (FRIGF group), and even absent in the normally fed animals (CIGF group). And indeed, despite positive correlating adipose leptin and IGF-1 expression, a causal relation has not been shown [17, 18]. In contrast, a 6-day peripheral infusion (s.c.) of rhIGF in adult male rats (1 mg/day) or in male hypophysectomized adult rats (300 µg/day) has been shown to reduce fat mass, and suppress leptin mRNA and serum leptin levels [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, GH treatment increases leptin levels [16] and leptin mRNA abundance in normal male cattle exhibiting a positive IGF-1 response to GH [17]. But although adipose leptin and IGF-1 expression were highly correlated, a causative or mediatory relation was not proven [17, 18]. Hence, the actions of GH, IGF-1 and leptin might be amplified mutually as they control growth and the accrual in muscle mass.…”
Section: Introductionmentioning
confidence: 99%
“…3 Overall a typical pattern was found: patients reported an inadequate diet plan and minimal physical activity; parental obesity was common and for most patients obesity began in adulthood. 31 The clinical indexes selected a priori (age of onset, parental obesity, degree of obesity, type of body fat distribution, carbohydrate craving, binge eating behaviour with purging and initial weight loss) are commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…31 The presence of other pathology as well as pharmacological drug use was also speci®cally assessed. Carbohydrate craving and binge eating behaviour with purging were assessed on a yesano basis from an openend interview by one of us who is experienced in the evaluation of obese patients, and generally following the Interview for Diagnosis of Eating Disorders (IDED).…”
Section: Methodsmentioning
confidence: 99%